Effect of temperature and concentration of industrial waste graphene on rheological properties of water based mud - Putra, Putri Humairah Monashofian (IOP PUBLISHING LTD, 2020)
It is no secret that nano technology has been widely applied in various industries. In the upstream oil and gas industry, nanoparticle technology has received widespread attention due to its ability to enhance drilling fluid properties; thus improves drilling efficiency and reduces the overall operation cost. The objective of the study is to investigate the effects of temperature and concentration of graphene retrieved from unwanted industrial waste on rheological and filtration properties of the water based drilling mud (WBM). It is known that graphene is very expensive. At the same time, the availability and abundance of industrial carbon based waste presents an opportunity to extract graphene from unwanted, inexpensive waste and utilise it to improve the drilling fluid properties. Three types of drilling fluids are formulated (basic WBM, WBM plus commercial graphene and WBM plus waste graphene) and tested based on the recommended API 13B-1 practice. Both commercial and waste graphene concentration was varied at 0.05, 0.1 and 0.2 ppb. For each concentration, the mud rheological and filtration properties were measured before and after aging for 16 hours at different temperature of 200 degrees F, 225 degrees F and 250 degrees F while the pressure was fixed at 500 psi. Results showed that the addition of small concentration of graphene nanoparticles increases the plastic viscosity (PV), yield point (YP), and improved the API and HPHT filtrate loss volume. However further increment in concentration caused the filtration property to deteriorate hence 0.05 ppb was taken as the optimum amount. It reduced the filtration loss by 8.43% at API condition and 18.57%, 13.82% and 14.06% at 200 degrees F, 225 degrees F and 250 degrees F respectively.